(untitled) (Journal of Medicine, 2009)
Leprosy could be best understood as two conjoined diseases. The first is a chronic mycobacterial infection that elicits an extraordinary range of cellular immune responses. The second is lepra reaction, whose course and sequelae often extend many years beyond the cure of the infection and may have severely debilitating physical, social, and psychological consequences. Type-2 lepra reaction is also termed Erythema nodosum leprosum (ENL) regardless of the site of involvement, which is in turn a Coomb and Gell Type III hypersensitivity reaction. The paradox of ENL is that it can be a life-threatening disorder and requires control with immunosuppression which may itself pose life-threatening risks for patients Indian studies found its prevalence rate of almost 50% in those with LL and 9% in BL cases and the mean time to presentation with ENL was 3.7 months after starting multi-drug therapy (MDT). Hitherto we report a severe and steroid dependent case of chronic ulcerated ENL, not only occurred sixteen years after successful treatment of lepromatous leprosy, but also had an unusual initial presentation of arthritis. To the best of our knowledge, ENL for such a prolonged period of 15 years was not reported earlier. Â doi:10.3329/jom.v10i1.2002 J Medicine 2009; 10: 31-33